2010
DOI: 10.1016/j.jpsychores.2010.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Latent class analysis of functional somatic symptoms in a population-based sample of twins

Abstract: Objective-This study aimed to investigate empirically how and in what way individuals with symptoms of functional somatic syndromes should be classified. We also aimed to look into genetic and environmental influences on the classification.Method-A total of 28531 twins aged 41-64 underwent screening interviews via a computerassisted data collection system from 1998 to 2002. Nine functional somatic symptoms (abnormal tiredness, general muscular pain, recurrent abdominal discomfort, back pain, gastroesophageal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 34 publications
2
68
2
6
Order By: Relevance
“…The findings of symptom profiles with no/few symptoms and with multiple symptoms were comparable with previous findings, [9][10][11][12][13][14] while only two of the previous studies also found symptom profiles defined by specific symptoms. 11,12 However, the number and description of the profiles differed from our findings except for an MS/pain profile, 11,12 a GI profile, 11,12 and an MS + GI profile.…”
Section: Relation To Other Studiessupporting
confidence: 90%
See 3 more Smart Citations
“…The findings of symptom profiles with no/few symptoms and with multiple symptoms were comparable with previous findings, [9][10][11][12][13][14] while only two of the previous studies also found symptom profiles defined by specific symptoms. 11,12 However, the number and description of the profiles differed from our findings except for an MS/pain profile, 11,12 a GI profile, 11,12 and an MS + GI profile.…”
Section: Relation To Other Studiessupporting
confidence: 90%
“…[9][10][11][12][13][14] Thus, 2, 13,14 3, 9,10 5, 12 and 11 11 profiles have been identified either based merely on numbers of symptoms 9,10,13,14 or based on number, site, and type of symptoms. 11,12 However, all the studies differed considerably in material and methods. Only two of the studies were conducted on a population-based sample, 12,14 while the others included more selected populations, eg, patients from primary or secondary care.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 While commonly co-occurring with mood and anxiety disorders, research suggests that, although functional somatic disorders are related and potentially interact with psychological conditions, they are independent. 5 The syndrome is characterised by its hallmark features of widespread somatic pain and deep tissue tenderness, which result from sensitisation of neural pain pathways.…”
Section: Introductionmentioning
confidence: 99%